'There Is Nothing There for Us and Nothing for the Future': Deindustrialization and Workplace Occupation, 1981–1982. Issue 1 (1st April 2021) - Clark, Andy
Abstract : This article draws on research into three female-led occupations that occurred across central Scotland in 1981 and 1982. The actions at Lee Jeans, Lovable Bra and Plessey Capacitors were each in response to closure and relocation and, crucially in the context of this time period, were at least partly successful in opposing full closure. The piece considers the uses and limitations of mobilization theories in accounting for the collective action that emerged at the plants. Rejecting the individualistic frameworks that place extensive importance on injustice, it is suggested that the immediate impacts of manufacturing decline through the process of deindustrialization were a crucial factor in sustaining the action. Through an analysis of the statements made by the workers, their leaders and supporters at the time, along with an examination of oral-history interview narratives, the argument develops that these disputes were not localized actions at one site against one plant closure. By placing the factories and the workers within the social and economic contexts in which they took action, the research indicated that the process of collective action was dynamic and motivations were inevitably multiple, but that the detrimental impacts of deindustrialization – particularly as they related to the future of the localities – was crucial.